2007
DOI: 10.2116/analsci.23.963
|View full text |Cite
|
Sign up to set email alerts
|

Strong Molecular Aggregation of Neutral Carriers Bearing Perfluoroalkyl Chains in Liquid-Crystalline Ion-Sensor Membranes

Abstract: A liquid-crystalline benzocrown ether, 4′-[(4″-1,1,2,2-tetrahydroperfluorooctyloxy)biphenyloxycarbonyl]benzo-15-crown-5, was used as a neutral carrier of ion-selective electrodes (ISEs) to elucidate the effect of highly ordered assembling of the neutral carrier on the sensor properties through fluorophilic interactions. The properties for the membrane and the resulting ISEs based on a benzocrown ether bearing a perfluoroalkyl chain were compared with those based on the corresponding crown ether bearing an alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several publications reported very interesting studies regarding polymeric membrane based electrochemical sensors [20][21][22][23][24][25][26]. Schwake et al applied AFM to study the origin of asymmetry potentials observed with ion-selective polymer matrix membranes [22].…”
Section: Doi: 101002/elan201100521mentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications reported very interesting studies regarding polymeric membrane based electrochemical sensors [20][21][22][23][24][25][26]. Schwake et al applied AFM to study the origin of asymmetry potentials observed with ion-selective polymer matrix membranes [22].…”
Section: Doi: 101002/elan201100521mentioning
confidence: 99%
“…AFM and X-rayphotoelectron spectroscopy in combination with scanning electron microscopy, secondary ion mass spectrometry, and electrochemical impedance spectroscopy were employed to study the physical and chemical integrity of solid-contact conductive polymeric ion sensors [25]. Molecular aggregation of neutral carriers bearing perfluoro alkyl chains in liquid-crystalline ion-sensor membrane has been studied by AFM and fluorescence measurements [20]. The roughness exponents of polypropylene and polystyrene were determined by examining the topography and polymeric fracture surfaces using AFM [26].…”
Section: Doi: 101002/elan201100521mentioning
confidence: 99%
“…They have enjoyed widespread use in various areas of science and technology [2][3][4][5][6] ever since the first preparation of the ligands by Pederson [1]. From a surfactant science viewpoint, crown ethers functionalized with pending alkyl groups are special ionophores allowing ion transport across lipophilic barriers [7,8]. The attachment of lipophilic long-chain alkyl groups allows crown ethers to acquire some amphiphilic properties [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Properties of the whole membrane matrix such as impedance, membrane resistance, dielectric constant, ionic conductivity, chronoamperometric and chronopotentiometric method, and second-harmonic generation (SHG) have been well documented. [6][7][8][9][10][11][12][13][14] Microscopic analyses with Fourier transform infrared spectroscopy using the attenuated total reflectance (FTIR-ATR) technique, 15,16 atomic force microscopy (AFM), 17 scanning electron microscopy (SEM), 18 and scanning electrochemical microscopy (SECM) 19 and surface analyses with spatial imaging photometer (SIP), 20 X-ray photoelectron spectroscopy (XPS), 18,21 and hyperspectral imaging 22 have also been utilized to elucidate the properties of the whole membrane matrix. Some attempts to elucidate the behaviors of the components included in the potentiometric liquid membranes have been made by the high resolution 13 C NMR or 1 H NMR analyses in solutions.…”
mentioning
confidence: 99%